Mediating Role of Self-Efficacy in the Effect of Cognitive Flexibility on Academic Motivation - Isler, Esra; Yucel-Toy, Banu (UNIV CHICAGO PRESS, 2026)
Middle school students are subject to considerable stress due to both adolescence and national high school entrance exam preparation in Turkiye. In this context, cognitive flexibility exerts a significant influence on both self-efficacy and academic motivation. This study examines the mediating role of self-efficacy in the relationship between cognitive flexibility and academic motivation. In this correlational study, a sample of 480 middle school students from Istanbul was selected using multistage sampling techniques. The mediation analyses revealed that cognitive flexibility significantly predicts academic, social, and emotional self-efficacy and all subdimensions of academic motivation. Notably, academic self-efficacy exhibits a full or partial mediation effect in the relationship between cognitive flexibility and all subdimensions of academic motivation. Emotional self-efficacy demonstrates partial mediation only in predicting identified regulation and amotivation. The present study is exploratory; consequently, it is anticipated that the results will provide a foundation for subsequent confirmatory studies.
Keywords: ACHIEVEMENT; ADOLESCENTS; STRATEGIES; Education & Educational Research